2013
DOI: 10.3945/ajcn.113.058248
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of tea consumption on attention and mood

Abstract: Tea has historically been associated with mood and performance benefits, such as relaxation and concentration. This review summarizes the research on the acute effects of tea, and its ingredients theanine and caffeine, on attention and mood. Consistent with abundant research on the benefits of caffeine, the performance benefits of tea were identified in a number of studies, with particularly consistent evidence for improved attention. Tea consumption also consistently improved self-reported alertness and arous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 88 publications
1
42
0
Order By: Relevance
“…Besides, antidiarrheal properties of black tea has been demonstrated in rodents (Besra et al, 2003;Hiller and Melzig, 2010). The additional CNS stimulant properties of black tea (Einother and Martens, 2013) might be beneficial for lethargic calves. The antibacterial, antiadhesive, antidiarrheal and spasmolytic properties of black tea may be beneficial in gastrointestinal diseases.…”
Section: Plants In Diseases For Which Antimicrobial Treatments Are Ofmentioning
confidence: 98%
“…Besides, antidiarrheal properties of black tea has been demonstrated in rodents (Besra et al, 2003;Hiller and Melzig, 2010). The additional CNS stimulant properties of black tea (Einother and Martens, 2013) might be beneficial for lethargic calves. The antibacterial, antiadhesive, antidiarrheal and spasmolytic properties of black tea may be beneficial in gastrointestinal diseases.…”
Section: Plants In Diseases For Which Antimicrobial Treatments Are Ofmentioning
confidence: 98%
“…There has been abundant research on the impact of caffeine on cognitive performance, but this evidence now includes several studies on tea consumption. In a review of the effects of tea consumption on attention and mood, Einöther and Martens (2013) reported a consistent finding that acute tea consumption improves attention, self-reported alertness and mental arousal. A recent systematic review and meta-analysis (Carnfield et al 2014) reported small to moderate effects on cognitive function and mood, which were attributable to L-theanine and caffeine.…”
Section: Cognitive Functionmentioning
confidence: 96%
“…Although caffeine is known to increase acetylcholine and dopamine transmission in the brain, implicated in attention and higher cognitive functions, less is known about L‐theanine, which is a highly bioavailable amino acid that is virtually unique to tea. Whereas caffeine is absorbed rapidly (peak plasma levels from 30 minutes after consumption; Einöther & Martens ), L‐theanine is absorbed more slowly, with reported peak plasma from 50 minutes (Van der Pijl et al . ), and so the acute effects may lag behind caffeine (Carnfield et al .…”
Section: Tea and Healthmentioning
confidence: 99%
“…Global tea consumption in 2018 was estimated at 273 billion liters per annum and projected to increase to 297 billion liters by 2021 (three times as much as coffee consumption rates) . The Tea Association of the USA estimates that some 159 million Americans consume tea on a daily basis , partly because of the beverage satisfaction as well as perceived health benefits . All tea comes from the leaves or buds of the Camellia sinensis plant and, based on fermentation processing, results in the main black, white, oolong, green, yellow, and pu‐erh tea classifications.…”
Section: Introductionmentioning
confidence: 99%